2014
DOI: 10.1186/s12862-014-0213-0
|View full text |Cite
|
Sign up to set email alerts
|

Recovering species demographic history from multi-model inference: the case of a Neotropical savanna tree species

Abstract: BackgroundGlaciations were recurrent throughout the Quaternary and potentially shaped species genetic structure worldwide by affecting population dynamics. Here, we implemented a multi-model inference approach to recover the distribution dynamics and demographic history of a Neotropical savanna tree, Tabebuia aurea (Bignoniaceae). Exploring different algorithms and paleoclimatic simulations, we used ecological niche modelling to generate alternative hypotheses of potential demographic changes through the last … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 43 publications
(50 reference statements)
2
19
1
2
Order By: Relevance
“…Both D. mollis and D. alata are pollinated by insects and have their seeds dispersed by mammals, in spite of differences in genetic diversity and distribution during the LGM. Still, the genetic diversity and genetic differentiation found for D. mollis was lower than for two other widely distributed non-legume tree species from central Brazil, Caryocar brasiliense (Collevatti et al, 2001) and Tabebuia aurea (Collevatti et al, 2014). In fact, there is evidence of 'range retraction' with multiple refugia during the LGM for C. brasiliense and a wide historical refugium across central Brazil for both C. brasiliense and T. aurea (Collevatti et al, , 2014, similar to what we found for D. mollis.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Both D. mollis and D. alata are pollinated by insects and have their seeds dispersed by mammals, in spite of differences in genetic diversity and distribution during the LGM. Still, the genetic diversity and genetic differentiation found for D. mollis was lower than for two other widely distributed non-legume tree species from central Brazil, Caryocar brasiliense (Collevatti et al, 2001) and Tabebuia aurea (Collevatti et al, 2014). In fact, there is evidence of 'range retraction' with multiple refugia during the LGM for C. brasiliense and a wide historical refugium across central Brazil for both C. brasiliense and T. aurea (Collevatti et al, , 2014, similar to what we found for D. mollis.…”
Section: Discussionsupporting
confidence: 51%
“…Still, the genetic diversity and genetic differentiation found for D. mollis was lower than for two other widely distributed non-legume tree species from central Brazil, Caryocar brasiliense (Collevatti et al, 2001) and Tabebuia aurea (Collevatti et al, 2014). In fact, there is evidence of 'range retraction' with multiple refugia during the LGM for C. brasiliense and a wide historical refugium across central Brazil for both C. brasiliense and T. aurea (Collevatti et al, , 2014, similar to what we found for D. mollis. These differences in demographic history and phylogeographical patterns between savanna tree species highlight the complexity of the biogeographical processes in the Cerrado biome.…”
Section: Discussionsupporting
confidence: 51%
“…Hijmans & Graham, ; Pliscoff et al ., ). Coupling population genetics assessment and niche modelling is a valuable strategy to investigate the influence of climate changes on intraspecific genetic diversity (Diniz‐Filho et al ., ; Collevatti et al ., ; Diniz‐Filho, Soares & Telles, ). Intraspecific variation is widely considered to have great conservation relevance, as intraspecific variation affects the evolutionary potential of this species.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, species distribution modelling techniques projected to past, present and future climatic conditions have been used to understand current geographical and genetic diversity distribution of different species. By linking the patterns of geographical and genetic diversity distribution, it is possible to identify areas of climate stability and predict the impacts of climate changes on species genetic diversity (Thuiller et al ., ; Collevatti, Nabout & Diniz‐Filho, ; Espíndola et al ., ; Collevatti et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…For instance, European oaks show fast migration, adaptation and extensive gene flow during the Quaternary that allowed them to survive and track suitable habitats in the past (see (Alberto et al., for a review). In Neotropics, the pollen fossil records have also shown modifications in vegetation community, with restoration of plant populations after the last glacial maximum, such as those associated with swamps (e.g., Behling & Hooghiemstra, ; Salgado‐Labouriau et al., ), which may indicate that Neotropical species also tracked suitable habitats or even survived in refuges (e.g., Collevatti et al., ; Collevatti, Lima‐Ribeiro, et al., ; Collevatti, Terribile, Rabelo, & Lima‐Ribeiro, ; Lima, Lima‐Ribeiro, Tinoco, Terribile, & Collevatti, ).…”
Section: Introductionmentioning
confidence: 99%